An innovative solution for the dynamic response of buried pipelines in layered transversely isotropic soil under pavement structures. (March 2022) - Yang, Linqing; Han, Zejun; Guo, Chengchao; Cao, Dingfeng; Ni, Pengpeng; Wang, Fuming
Abstract: The interaction between a buried pipeline and the surrounding soil under dynamic loads has attracted the attention of researchers. In this paper, a modified scaled boundary finite element method (SBFEM) based on the mechanical derivation method is proposed to determine the dynamic response of the buried pipeline in layered transversely isotropic soil under the pavement structure. A similarity line that replaces the similarity centre of the conventional method was introduced in the modified SBFEM. As a result, a new stiffness matrix equation was established for layered soil. The accuracy of the proposed algorithm was confirmed through numerical examples. Therefore, the effects of the thin layer elastic modulus, pipeline cushion thickness, pipeline radius, pipeline buried depth, and location of the cavity under the pipeline on the dynamic response of pipelines were studied under dynamic pavement loads. The parametric analysis gives a reliable numerical solution for engineering problems.